Profil Dry Eye pada Penderita Diabetes Melitus - ; Ahmad Ashraf Amalius; Andi Akhmad Faisal (Majalah Oftalmologi Indonesia, 2022)
Aim: To evaluate dry eye syndrome patients based on meibomian gland evaluation, tear break up time test, Schirmer test, and ocular surface disease index form the diabetic mellitus patients. Materials And Methods: A Cross Sectional Study used to determine the profil of dry eye Syndrome on 15 diabetic mellitus patients in Eye center Hasanuddin University from December 2019 until February 2020  Results: 15 participants have included in this study. From the meibomian gland evaluation, there are 10 participants with mild dry eye. From the tear break up time test, there are 10 participants with dry eye. From the Schirmer test, there are 8 participants having dry eye on Schirmer 1 test and 8 participants with dry eye on Schirmer 2 test. And, from the ocular surface disease index, 11 participants with severe dry eye disease were identified. Conclusion: Patients with diabetes mellitus have a high potential for dry eye. Dry eye screening examinations such as tear break up time and Ocular Surface Disease Index (OSDI) are recommended to use in patients with diabetic retinopathy.